A new model for airport passenger segmentation. (July 2015) - Harrison, Anna; Popovic, Vesna; Kraal, Ben
Recent changes in the aviation industry and in the expectations of travellers have begun to alter the way we approach our understanding, and thus the segmentation, of airport passengers. The key to successful segmentation of any population lies in the selection of the criteria on which the partitions are based. Increasingly, the basic criteria used to segment passengers (purpose of trip and frequency of travel) no longer provide adequate insights into the passenger experience. In this article, we propose a new model for passenger segmentation based on the passenger core value, time . The results are based on qualitative research conducted in situ at Brisbane International Terminal during 2012–2013. Based on our research, a relationship between time sensitivity and degree of passenger engagement was identified. This relationship was used as the basis for a new passenger segmentation model, namely, airport enthusiast (engaged and non-time sensitive), time filler (non-engaged and non-time sensitive), efficiency lover (non-engaged and time sensitive) and efficient enthusiast (engaged and time sensitive). The outcomes of this research extend the theoretical knowledge about passenger experience in the terminal environment. These new insights can ultimately be used to optimize the allocation of space for future terminal planning and design.